2020
DOI: 10.1016/j.ijthermalsci.2019.106204
|View full text |Cite
|
Sign up to set email alerts
|

A new process for the determination of the Soret coefficient of a binary mixture under microgravity

Abstract: In the presence of a gravity field or under microgravity, pure thermo-diffusion leads to very weak species separation in binary mixtures. To increase the species separation in the presence of gravity, many authors use thermo-gravitational diffusion in vertical columns (TGC). For a given binary mixture, the species separation between the top and the bottom of these columns depends on the temperature difference, ΔT, imposed between the two vertical walls facing each other, and the thickness, H, between these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The present work is an extension of the study performed by Mojtabi [9] with various mixtures, from binary to n-component mixtures. An application with a ternary mixture was presented.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The present work is an extension of the study performed by Mojtabi [9] with various mixtures, from binary to n-component mixtures. An application with a ternary mixture was presented.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, Mojtabi [9] showed that it is possible to significantly increase the importance of species separation for binary mixtures, in microgravity, using forced convection obtained by a uniform translational displacement of the isothermal walls maintained at T h and T c respectively, with ∆T = T h − T c . In this new configuration, the species separation is several orders of magnitude greater than the one obtained in thermo-gravitational columns (TGC).…”
Section: Introductionmentioning
confidence: 99%
“…It is to note here that, except some experimental tests devoted to analyse some specific behaviors [4,5], most of these studies have addressed the measurement of the thermal diffusion coefficients of various multicomponent mixtures [6−9]. To this end, novel methods based on Thermogravitational [6], electrochemical impedance spectroscopy [7], thermal lens spectrometry [8] and microgravity [9] process have been presented and adopted in these studies. Recent experimental techniques used to simulate the thermal diffusion effect in binary and ternary liquid mixtures have been described and interpreted in the review conducted by Köhler et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results were compared with the experimental values obtained on the Earth. Mojtabi [19] presented a new process for the determination of the Soret coefficient of a binary mixture under microgravity.…”
Section: Introductionmentioning
confidence: 99%